2009
DOI: 10.1002/cbf.1557
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of 2‐methoxyestradiol on cell numbers, morphology, cell cycle progression, and apoptosis induction in oesophageal carcinoma cells

Abstract: The influence of 2-methoxyestradiol (2-ME) was investigated on cell numbers, morphology, cell cycle progression, and apoptosis induction in an oesophageal carcinoma cell line (WHCO3). Dose-dependent studies (1 x 10(-9)M-1 x 10(-6)M) revealed that 2-ME significantly reduced cell numbers to 60% in WHCO3 after 72 h of exposure at a concentration of 1 x 10(-6)M compared to vehicle-treated cells. Morphological studies entailing light-, fluorescent-, as well as transmission electron microscopy (TEM) confirmed 2-ME's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…In particular, our data indicated an involvement of caspase-8 and not of caspase-9 in the apoptotic cascade proteolysis, thus suggesting the activation of the extrinsic pathway. However, our evidence that mitochondria from 2-ME treated cells have an altered distribution, in line with the reported increase in mitochondria aggregating around the nuclear envelope (Thaver et al 2009), could support an effect of the drug on mitochondria. In fact, it has been reported that 2-ME promotes the release of cytochrome c and the translocation of Bax protein to mitochondria in pancreatic cancer cells (Qanungo et al 2002).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In particular, our data indicated an involvement of caspase-8 and not of caspase-9 in the apoptotic cascade proteolysis, thus suggesting the activation of the extrinsic pathway. However, our evidence that mitochondria from 2-ME treated cells have an altered distribution, in line with the reported increase in mitochondria aggregating around the nuclear envelope (Thaver et al 2009), could support an effect of the drug on mitochondria. In fact, it has been reported that 2-ME promotes the release of cytochrome c and the translocation of Bax protein to mitochondria in pancreatic cancer cells (Qanungo et al 2002).…”
Section: Discussionsupporting
confidence: 83%
“…In fact, given that drug resistance of cancer cells is often correlated with the evasion of apoptosis, a major goal in cancer research is to selectively increase the susceptibility of cancer cells to apoptosis-based strategies (Giansanti and Scovassi 2008). Previous studies have reported the ability of 2-ME to induce apoptosis in various human cancer cell lines, by triggering both the extrinsic (Pribluda et al 2000;LaValle et al 2003;Mooberry et al 2003;Shimada et al 2004;Kato et al 2008;Thaver et al 2009) and intrinsic pathway (Yue et al 1997;Attalla et al 1998, Schumacher andNeuhaus 2001;Bu et al 2002;Mooberry 2003;Shimada et al 2003;Gao et al 2005;Zou et al 2006;Fukui and Zhu 2009). The activation of caspase-independent apoptosis by 2-ME has also been explored.…”
Section: Discussionmentioning
confidence: 99%
“…2ME failed to advance to United States Food and Drug Administration approval because of its low efficacy [1][2][3][4]. It also shows rapid metabolic degradation and has limited bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…Although the molecular mechanisms for FGF8b overexpression in prostate and breast cancers are not fully understood, the human sex hormone androgen (Tanaka et al, 1992) is known to play a key role, even in the case of breast cancer (Castellano et al, 2010Park et al, 2010 (in addition to prostate cancer (Gnanapragasam et al, 2002)). Similar findings in esophageal cancer, which has recently found to be androgen-related (Yamashita et al, 1989;Awan et al, 2007;Thaver et al, 2009), also revealed that FGF8b overexpression is linked to androgen signaling (Tanaka et al, 2001;Awan et al, 2007). With the limited number of cancer types being investigated thus far, it is unclear whether FGF8b is involved in the carcinogenesis of other human malignancies, especially in those hormone-unrelated cancers.…”
Section: Introductionmentioning
confidence: 78%